Effect of Rota Plant Extracts on the SIRT3 Sertoin-3 Concentration in the Alzheimer Patients’ Blood (International Journal of Scientific Research in Science and Technology, 2024)
We induced Alzheimer’s disease in a group of mices, after which they were treated with extracts of the Ruta plant, which included a group of chemical compounds, including alkaloids, flavonoids, and the oil extract. The results of treatment with the Ruta plant extract showed a significant effect on the biochemical variables studied, as the Ruta extracts led to raising the concentration of the sirtuin3 enzyme to good levels with a significant difference from the affected group. As for the flavonoid extract, it was the most efficient by recording the lowest average of the enzyme between the groups. Infected.